Acute and chronic effects of resistance exercise training among young adults with and without analogue Generalized Anxiety Disorder: A protocol for pilot randomized controlled trials. (March 2020) - Gordon, Brett R.; McDowell, Cillian P.; Lyons, Mark; Herring, Matthew P.
Abstract: Objectives: Recent meta-analyses support the chronic anxiolytic effects of resistance exercise training (RET) among women with diagnosed Generalized Anxiety Disorder (GAD). However, the effects of RET among those with subclinical, or analogue, GAD (AGAD) is unknown. The purpose of the pilot randomized controlled trial (RCT) detailed in this protocol was to quantify the acute and chronic effects of RET on signs and symptoms of GAD among young adults with and without AGAD. Methods: This protocol details the full methods of two parallel, RCTs of an eight-week RET intervention compared to a wait-list control condition among young adults with and without AGAD. AGAD status was determined using validated cut-scores for both the Psychiatric Diagnostic Screening Questionnaire GAD subscale (≥6) and the Penn State Worry Questionnaire (≥45). The ecologically-valid RET was designed according to World Health Organization and American College of Sports Medicine guidelines. The primary outcome was AGAD status, assessed pre- and post-intervention. Secondary outcomes were assessed weekly. Two acute RET trials were nested within the design at pre- and post-intervention to determine response and change in response to a single bout of RET. Conclusions: This pilot RCT examines the effect of an ecologically-valid RET intervention among young adults with subclinical levels of GAD. Given that GAD most often emerges during young adulthood, and young adults who display elevated subclinical symptoms are more likely to develop clinically significant psychopathology, investigating the effects of RET among individuals with emerging signs and symptoms of an anxiety disorder is particularly important. Trial registration: ClinicalTrials.gov Identifier: NCT04116944. Highlights: RCT for 8 week guidelines based RET among young adults with/without Analogue-GAD. First RCT to examine ecologically valid RET among young adults with elevated worry. Findings will have implications for efficacy of RET as augmented treatment for GAD.